The Construction of the Meaning of Cafe for Millennials (Phenomenology in the Construction of the Meaning of Hanging Out for Millennials-Café User around Campus) - Musfialdy Musfialdy; Rika Lusrivirga (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Cafes are places where people drink coffee or other drinks that don't contain alkhohol. The purpose of this study is about cafe users on students born between 1981-1999 (y generation or millennial generation). Analyzing the meaning of cafes symbols on the millennial around campus. The theory used is theoretical phenomenon, where reality is constructed according to the perspective of the individual who is research informant. Another theory is the theory of social construction of reality that social processes through action and interaction, the individual creates a continuous, subjective, shared reality. The study is using qualitative methodologies with a phenomenological method. The study informants were students of the communication program study s-2 class 2019 postgraduate programs, Faculty of Communication Sciences, Padjadjaran University. Data gathering techniques through observation, interviews, secondary data sources. Research facility around the unpad campus, Jatinangor, West Java. This research shows the meaning in cafes obtained the word